2009
DOI: 10.1590/s1415-43662009000600003
|View full text |Cite
|
Sign up to set email alerts
|

Produção de capins cultivados sob pastejo em diferentes lâminas de irrigação e estações anuais

Abstract: Objetivou-se, com o presente trabalho, avaliar a produtividade de matéria seca de seis gramíneas, sob efeito de diferentes lâminas de irrigação, em diferentes estações do ano. O experimento foi conduzido em esquema de parcelas subsubdivididas havendo, nas parcelas seis gramíneas (Xaraés, Mombaça, Tanzânia, Pioneiro, Marandu e Estrela), nas subparcelas, seis lâminas de irrigação (0, 18, 45, 77, 100 e 120% da referência) e, nas subsubparcelas, as estações (outono/inverno e primavera/verão) no delineamento inteir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
(13 reference statements)
0
7
0
3
Order By: Relevance
“…These experiments were conducted in locals of low latitude and altitude: 18° 47' and 223 m for Governador Valadares, Minas Gerais, and 11° 45' and 287 m in Gurupi, Tocantins, respectively. According to Alencar et al (2009b), the winter temperature in these regions is higher than 15 ºC and under conditions of average winter annual temperatures superior to this value, pasture growth rate is not very reduced. In the first evaluations of the experiment during the rainy period, there was no difference between species, or there was higher production of dry forage mass of xaraes grass on the average of doses/strategies of N application in relation to tifton 85 (Table 5).…”
Section: Resultsmentioning
confidence: 97%
“…These experiments were conducted in locals of low latitude and altitude: 18° 47' and 223 m for Governador Valadares, Minas Gerais, and 11° 45' and 287 m in Gurupi, Tocantins, respectively. According to Alencar et al (2009b), the winter temperature in these regions is higher than 15 ºC and under conditions of average winter annual temperatures superior to this value, pasture growth rate is not very reduced. In the first evaluations of the experiment during the rainy period, there was no difference between species, or there was higher production of dry forage mass of xaraes grass on the average of doses/strategies of N application in relation to tifton 85 (Table 5).…”
Section: Resultsmentioning
confidence: 97%
“…Considering this prerogative, Alencar et al (2009a) evaluated the productivity of dry matter of different grass cultivars, under the effect of different irrigation depths, in different seasons of the year, in Governador Valadares, MG, and observed that the irrigation depths affected the productivity of dry matter of the grasses and recommended the irrigation depths of 120, 120, 120, 80, 80 and 74 % of the reference depth for the grasses Mombaça, Pioneiro, Marandu, Xaraes, Tanzania and Estrela, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Conforme alguns autores (LYRA et al, 2008;SILVA et al, 2008;ALBUQUERQUE Filho et al, 2009;ALENCAR et al, 2009;SANTANA et al, 2009;LIMA JÚNIOR et al, 2010;OLIVEIRA et al, 2011), o polinômio de segundo grau é uma das equações matemáticas mais utilizadas como função de produção; no entanto, as funções de produção devem, em geral, ser usadas em intervalos convenientes, isto é, sem exceder níveis do insumo economicamente razoáveis. Além disso, para a…”
Section: Figure 2 -Grain Yield (A) Real Evapotranspiration-etr (B) Aunclassified